Analysis of Marketing Strategies to Enhance the Competitiveness of the Coffin Business in Kaweng Village, Kakas Subdistrict - Kentey, Julia; Tampi, Johny R E; Walangitan, Olivia F Christine (Productivity, 2026)
The purpose of this study is to identify the marketing strategies employed by coffin business owners in Kaweng Village, Kakas Subdistrict, to enhance their business competitiveness. The findings of this study indicate that coffin business owners in Kaweng Village implement various marketing strategies to enhance competitiveness, including product differentiation, customer relationship management, and digital marketing. Despite facing challenges such as fluctuating raw material prices and limited production capacity, businesses have successfully leveraged their local networks and optimized pricing strategies to sustain demand. The study also highlights the importance of innovation, particularly in premium coffin designs with customized features, to attract a broader customer base. Furthermore, the use of social media has emerged as an effective promotional tool, allowing businesses to expand their market reach beyond the local area. These insights provide valuable recommendations for improving marketing strategies and ensuring the long-term sustainability of the coffin-making industry in the region.